2017
DOI: 10.1007/s10151-017-1620-1
|View full text |Cite|
|
Sign up to set email alerts
|

Distal Doppler-guided transanal hemorrhoidal dearterialization with mucopexy versus conventional hemorrhoidectomy for grade III and IV hemorrhoids: postoperative morbidity and long-term outcomes

Abstract: Our results showed that Doppler-guided THD is not inferior to conventional excisional hemorrhoidectomy for advanced hemorrhoidal disease in terms of postoperative complications and long-term recurrence of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…Results showed lower early postoperative pain in THD group, but although the grade of hemorrhoids was significantly reduced after 1 year for both methods, there was a trend to more patients with remaining grade II hemorrhoids in THD group ( p = 0.06). The recent studies of Trenti et al, 2017 [5] and De Nardi et al, 2014 [6] with relatively long follow-up (about 24 months), showed similar postoperative pain and morbidity, and a similar long-term cure rate of THD and CH. Meta-analysis of Xu et al (2016) including 4 randomized trials, reported that there are no statistically significant differences in total complications, recurrence and reoperation rates.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Results showed lower early postoperative pain in THD group, but although the grade of hemorrhoids was significantly reduced after 1 year for both methods, there was a trend to more patients with remaining grade II hemorrhoids in THD group ( p = 0.06). The recent studies of Trenti et al, 2017 [5] and De Nardi et al, 2014 [6] with relatively long follow-up (about 24 months), showed similar postoperative pain and morbidity, and a similar long-term cure rate of THD and CH. Meta-analysis of Xu et al (2016) including 4 randomized trials, reported that there are no statistically significant differences in total complications, recurrence and reoperation rates.…”
Section: Discussionmentioning
confidence: 98%
“…In order to reduce them, a Doppler-guided transanal hemorrhoidal dearterilization (THD) has been introduced as an effective alternative since the 90’s [14]. There is an increasing number of studies comparing THD and CH, but the focus of most of them is the early postoperative results [57]. The data about long-term outcomes and recurrence rates is still limited [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trenti et al (2017) 21 evaluated 83 patients, of whom 49 underwent Doppler-guided dearterialization and 34, CH. It was observed that the 30-day postoperative surgical morbidity was 26.5% in the patients submitted to Doppler-guided dearterialization, vs. 8.82% in those who underwent CH.…”
Section: Discussionmentioning
confidence: 99%
“…However, SH had a lower recurrence rate compared with THD. Trenti et al (19) conducted a randomized controlled study of THD and TS, suggesting that THD is not inferior to conventional excisional hemorrhoidectomy for advanced hemorrhoidal disease in terms of postoperative complications and long-term recurrence of symptoms.…”
Section: Discussionmentioning
confidence: 99%